2014
DOI: 10.1002/nau.22662
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microcirculation: Non-invasive anatomical examination of the micro-vessel architecture, tortuosity and capillary density

Abstract: This is the first report on both microcirculatory architecture and quantitative microcirculatory parameters of the vagina with the use of SDFI. Micro-vessels of the vagina show a recognizable pattern in our study population of young, healthy women. SDFI gives a reproducible assessment of the vaginal microcirculation offering the researcher a wide field of applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…Therefore, it is not possible to use these programs for analysis of vaginal images, and it is impossible to compare density parameters between different architecture scores. In this study, we calculated capillary density by manually counting loops per field of view in architecture score 1 and 2 dominant tissue (as was validated by Weber et al). Unfortunately, with this method, capillary density cannot be calculated in architecture score 2 and 3 tissue, since capillary loops were limited to absent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is not possible to use these programs for analysis of vaginal images, and it is impossible to compare density parameters between different architecture scores. In this study, we calculated capillary density by manually counting loops per field of view in architecture score 1 and 2 dominant tissue (as was validated by Weber et al). Unfortunately, with this method, capillary density cannot be calculated in architecture score 2 and 3 tissue, since capillary loops were limited to absent.…”
Section: Discussionmentioning
confidence: 99%
“…This scoring system allows for classification of subepithelial vascular patterns . Microvascular architecture scores from each measurement site were examined and systematically classified with a score of 1, 2, or 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritoneal angioarchitecture was examined and classified as 1 of 3 types of vascular patterns, as validated and described by Weber et al [23]. These vascular patterns include the appearance of capillary loops (score 1), the appearance of capillary loops in combination with capillary networks (score 2), and the appearance of only capillary networks (score 3).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that the morphology, architecture, and capillary density of the vaginal microcirculation can be reliably and consistently quantified using sidestream dark‐field imaging (SDFI) in healthy young women . If, and to what extent, the vaginal microcirculation is altered in women with POP is at present unknown.…”
Section: Introductionmentioning
confidence: 99%